Monetary Incentives and Mood. (With Abstract) - Meloy Margaret G (May 2006)
Researchers have long debated the methodological necessity of monetary incentives in experimental research. The current work shows that financial incentives not only can fail to improve task performance but also can worsen it. Three studies verify that incentives can elevate mood and that this mood enhancement contributes to worsened task performance. The authors discuss implications for the use of incentives in experimental research.
Keywords: Monetary Incentives, Task Performance